2011
DOI: 10.1002/ptr.3539
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Armepavine Against Hepatic Fibrosis Induced by Thioacetamide in Rats

Abstract: The aim of this study was to investigate if armepavine (Arm, C₁₉H₂₃O₃N) could exert inhibitory effects against hepatic fibrosis in rats. A cell line of rat hepatic stellate cells (HSC-T6) was stimulated with tumour necrosis factor-α (TNF-α) to evaluate the inhibitory effects of Arm. Rats were injected with thioacetamide (TAA; 300 mg/kg, intraperitoneally) thrice a week for 4 weeks to induce hepatic fibrosis, with Arm (3 or 10 mg/kg) given by gavage twice a day. Liver sections were taken for western blotting, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…We showed that CnP markedly reduced the fibrosis in the rat liver. Previous reports showed that liver fibrosis induced by CCl 4 or TAA was suppressed by armepavine (29), follistatin (30), salvianolic acids (31) and other agents (32)(33)(34)(35)(36)(37). Compared to these compounds, suppression of liver fibrosis by CnP was much more significant; indeed, the effect of CnP was visible on the surface of the liver.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that CnP markedly reduced the fibrosis in the rat liver. Previous reports showed that liver fibrosis induced by CCl 4 or TAA was suppressed by armepavine (29), follistatin (30), salvianolic acids (31) and other agents (32)(33)(34)(35)(36)(37). Compared to these compounds, suppression of liver fibrosis by CnP was much more significant; indeed, the effect of CnP was visible on the surface of the liver.…”
Section: Discussionmentioning
confidence: 99%
“…After culturing for 24 hr, serum-starved cells were pretreated with Tan IIA (10 µM) or Sal B (200 µM) for 1 hr, then exposed to LPS for 15 min for harvesting NF-κB-p65 and MAPKs (ERK, JNK and p38), and exposed to LPS for 24 hr for harvesting α-SMA. Nuclear extracts of HSCs for NFκB-p65 translocation were prepared according to our previous study [29]. Whole cell protein extracts for measurement of ERK, JNK, p38 and α-SMA proteins were harvested with RIPA buffer.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, armepavine from N. nucifera has been found to be effective against hepatic fibrosis induced by thioacetamide in rats. The treatment of armepavine inhibited protein expression of α-smooth muscle actin, collagen type I and angiopoietin-1, H 2 O 2 production and nuclear translocation of NF-κB, JunD and C/EBPβ in TNF-α stimulated hepatic stellate cells (HSC-T6) (Weng et al, 2012).…”
Section: Pharmacological Reportsmentioning
confidence: 99%
“…Grienke et al, 2015) 4 (s)-armepavine Auto-immune(Ka et al, 2010) (Liu et al, 2007), hepatic fibrosis(Weng et al, 2012), Cell cycle arrest(Liu et al, 2004), SLE(Liu et al, 2006), Anti-melanogenesis(Morikawa et al, 2016) 5 …”
mentioning
confidence: 99%